Collaborative technique for wireless sensor network localization - BOUKHARI Nawel (University of M'Sila, 2024)
This thesis explores sensor networks, focusing on distributed algorithms for localization challenges. It addresses the need to determine node positions after random deployment, crucial for event localization. The proposed solution involves employing a mobile anchor with GPS units, moving within the area of interest, periodically broadcasting its location to assist unknown nodes in self-localization. A novel path planning model for mobile-based localization in WSNs is introduced, incorporating beacon points from five established paths (SCAN, HILBERT, S-type, Z-curve, and Σ-Scan) on the widely used square grid decomposition. Unknown sensor nodes estimate positions using APT and WCWCL-RSSI techniques. The simulation results demonstrate that the proposed model achieves exceptional accuracy, leading to a significant reduction in error rates when compared to alternative models. Moreover, it ensures maximum coverage with a lower path resolution value, indicating its effectiveness in optimizing localization outcomes. The thesis underscores the impact and importance of path parameterization in enhancing the quality of a localization .system with a mobile anchor node
تستكشف هذه الرسالة مسألة تحديد الموقع في شبكات الاستشعار اللاسلكية باستخدام الخوارزميات الموزعة. بعد النشر العشوائي للمستشعرات هنالك حاجة ماسة لمعرفة موقعها وخاصة من أجل معرفة مكان الأحداث. نقترح استخدام مستشعر خاص يكون يسمى مرساة، تتحرك المرساة داخل منطقة الاهتمام وفق مسار ،GPS متحركا و مزودا بوحدة معد مسبقا وتبث موقعها بانتظام لمساعدة المستشعرات غير معرفة الموقع في التحديد الذاتي لإحداثياتها. تقوم المستشعرات الغير معرفة الموقع بتقدير إحداثياتها باستخدام السؤال الذي حاولنا الإجابة عليه في هذه الرسالة هو ما هو .WCWCL-RSSI و APT تقنيات أحسن مسار يمكن أن تسلكه المرساة. قمنا في البداية باقتراح مجموعة من المعايير التي تسمح لنا بقياس جودة المسار. قمنا كذلك بدراسة و تحليل خمسة مسارات معتمدة على اقترحنا في .SCAN HILBERT, S-type, Z-curve, Σ-Scan : تقسيم منطقة الاهتمام الى مربعات الذي يجمع جميع نقاط البث للمسارات الخمسة Union-curve النهاية مسارا جديدا سميناه السابقة. تظهر نتائج محاكاة النموذج المقترح أنه يحقق دقة استثنائية، مما يؤدي إلى تقليل كبير في معدلات الخطأ مقارنة بالنماذج البديلة، علاوة على ذلك، يضمن تغطية كاملة مع دقة مسار أقل.
Keywords: Localization; Mobile anchor; Path planning model; Wireless sensor network; .Square grid decomposition; Beacon points; تحديد الموقع؛ مرساة متحركة؛ نموذج تخطيط مسار؛ شبكة الاستشعار اللاسلكية؛ تقسيم الشبكة المربعة؛ نقاط البث.